Labile N and the nitrogen management index of oxisols in the Brazilian cerrados - Westerhof, R; Vilela, Lourival; Ayarza, Miguel Angel; Zech, W. (International Center for Tropical Agriculture, 1999)
The effect of land use on the availability of soil nitrogen (N) was studied by separating total soil N into one labile and one stable fraction by oxidation and extraction of labile N with potassium permanganate. The nitrogen management index (NMI) was calculated according to Blair et al. (1995) for the carbon management index. In all systems, labile N released by potassium permanganate was a better indicator for nitrogen availability than were total and stable N. The NMI was a good indicator for N availability but gave no information on the total amount of N. In land-use system analysis, total N and labile N can be used together as a simple and rapid way to evaluate the nitrogen status of the soil. Legume-based pastures specifically increased the amount of labile N. Although soybeans had a dominant role in the continuous cropping systems studied, total N contents decreased, compared with native savanna. The availability of N under legume-based pastures and legume-based pasture/crop rotations was higher than under native savanna and continuous cropping systems.